The The Effect of TPACK-Based Image Media on Students' Critical Thinking Ability - Syamsul Ghufron; Nafiah; Mustofa; Kaswadi; Agus Darmuki (Universitas Pendidikan Ganesha, 2025)
Critical thinking skills and the Technological Pedagogical Content Knowledge (TPACK) framework have become key issues in contemporary education, especially in Indonesia. Despite advancements in critical thinking education, the integration of technology remains a challenge. This study investigates the impact of TPACK-based image media on the development of students’ critical thinking skills in writing instruction. The research employs a quasi-experimental design using a post-test only, non-equivalent control group approach. The subjects include 5th grade students from two public elementary schools in the southern Surabaya area, comprising an experimental group (38 students) using TPACK-based image media and a control group (36 students) using traditional blackboard media. Data were collected through interviews, observations, document analysis, and tests. Statistical and inferential analyses were applied to assess the data. The findings reveal significant differences between the two groups, with students in the experimental group demonstrating superior critical thinking abilities. The study concludes that TPACK-based image media positively affects students’ critical thinking skills, suggesting that enhancing technological proficiency is crucial for the effective application of this approach. The research implications emphasize the need for integrating digital literacy into critical thinking development in educational settings.